The Railway Children - Nesbit Edith (Lahore : Maqbool books, 2020)
The Railway Children by E. Nesbit is a heartwarming story about three siblings$1 (BRoberta (Bobbie), Peter, and Phyllis$1 (Bwho are forced to move to the countryside after their father is falsely accused of a crime and imprisoned. The family$1 (Bs new home is near a railway station, and the children quickly develop a deep fascination with the trains and the people who work there. Throughout the novel, the children make new friends, help those in need, and discover ways to unravel the mystery surrounding their father's disappearance. Their adventures involve acts of kindness, courage, and resourcefulness, ultimately leading to a heartening reunion with their father. The book emphasizes themes of family, loyalty, friendship, and the joy of discovery, while also promoting values like perseverance and compassion.s
Keywords: English : Novel